Pengembangan Sistem Informasi Pencatatan Riwayat Dan Notifikasi Penjadwalan Donor Darah Berbasis Website Menggunakan Framework Codeigniter - Rosalina Yani Widiastuti; Endang Setyawati; Angela Marici Uba Langobelen (INCODING: Journal of Informatics and Computer Science Engineering, 2021)
The Indonesian Red Cross is a national association organization in Indonesia that is engaged in the social and humanitarian field. One of PMI's main activities is blood donation. Currently, in handling the need for blood donors, UDD PMI Banyumas Regency has a system that helps in the donor process, namely SIMDONAR. SIMDONAR is an information system from the central IT provided to UDD PMI Banyumas Regency in the operation of blood donors, but in some aspects of blood donation, such as donor recording and notification of donor scheduling to donors, there is still no available so that it can run efficiently. Data collection in the blood donor history recording system still cannot be recorded properly, causing donors to also not be able to know the history of the last donor, when and how many times the donor has donated, there is also no notification of blood donor scheduling for donors, this makes the information conveyed to donors is incomplete so that donors are confused in taking action when to donate again. Therefore, to support the smooth running of the blood donor system, it is necessary to rebuild an appropriate information system that can provide a solution for the process of recording blood donation history at UDD PMI Banyumas Regency. The purpose of this system is to provide accurate and efficient information related to blood donation history records, and scheduling notifications to officers and donors. The benefit of this system is that it helps provide information related to donor history records for UDD PMI Banyumas Regency so that they can find out donor history records from donors, also helps donors to find out donor history or how many times the donor has donated blood. In this case, the system development method uses the prototype model method. Based on the results of the benefit test, the average value of the Efficiency value is 98.33%, the Usability value is 94.33%, the Correctness value is 95.56%, the Integrity value is 96.67%, and the Testability value is 96.67%. From the results of the benefit test, it can be concluded that the development of this system can be applied and used to facilitate the process of recording blood donor history and notification of blood donor scheduling at UDD PMI Banyumas Regency.